Entitled "THE MAGIC WAND": A novel treatment option for delayed replantation of an avulsed permanent tooth using injectable platelet-rich fibrin - Nanditha Suresh (Wolters Kluwer Medknow Publications, 2021)
Tooth loss can have not just a physical handicap but also a psychological bearing on an individual. Avulsion or complete displacement of the tooth from the socket can result due to various factors ranging from road traffic accidents to domestic abuse. Replantation of such avulsed teeth has been a topic of debate owing to the duration of extra oral time, storage medium and long term success. In this case report we discuss the successful replantation of an avulsed permanent tooth with an increased extra oral dry time using Injectable form of Platelet rich fibrin (i- PRF).